Creating Space For Thinking Together (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
The purpose of this afternoon gathering was to celebrate the launch of Community Engagement: A Critical Guide for Practitioners. The event was well attended by a diverse group of practitioners, activists, academics and students, all bearing their own understanding of the challenges and opportunities facing contemporary community engagement, and all willing to listen to the thoughts and views of others. This Guide is a timely resource and makes an excellent contribution to the field of practice; it has the potential to play a major role in helping us unpack the challenge we face to foster the type of community engagement that can help us to address some of the inequalities within our communities. The Guide can be used in its entirety to encourage dialogue and discussion or as stand-alone sessions. As well as being a really useful resource for those working with community groups, it also challenges practitioners to bring a critical lens to the nature of their own practice.